Abortion and unintended pregnancy in Pakistan: new evidence for 2023 and trends over the past decade - Susheela Singh; Octavia Mulhern; Zeba Sathar; Iqbal H Shah; Muhammad Rehan Niazi; Tahira Parveen; Ali Mohammad Mir (BMJ Global Health)
Background Despite induced abortion being highly legally restricted in Pakistan, studies in 2002 and 2012 showed that many women rely on abortion when faced with an unintended pregnancy. Following the 2012 study, concerted efforts were made to improve contraceptive services and to strengthen postabortion care. The availability and use of misoprostol also expanded in the past decade. Our primary objective was to provide new evidence on the rates of unintended pregnancy, induced abortion and postabortion care in 2023 and to assess trends in these outcomes since 2012.Methods This is a cross-sectional study based on a Health Professional Survey, and a nationally representative Health Facilities Survey, conducted in 2023. A widely applied methodology is used to estimate rates of abortion and unintended pregnancy. Data sources and methods are comparable across the 2012 and 2023 studies.Results In 2023, an estimated six million unintended pregnancies occurred and 64% of them or 3.8 (95% CI 2.2 to 6.4) million resulted in induced abortions. This corresponds to an annual unintended pregnancy rate of 100 and an induced abortion rate of 66 (95% CI 38 to 111) per 1000 women aged 15–49. There was no significant change in the unintended pregnancy rate, but the abortion rate increased by 25% between 2012 and 2023. In 2023, 697 913 women were treated for postabortion complications, corresponding to an annual rate of 12.1 (95% CI 6.4 to 16.5) per 1000 women ages 15–49. This treatment rate declined by 16% between 2012 and 2023.Conclusions The unintended pregnancy rate has remained stable in the past decade. However, Pakistani women are increasingly relying on abortion to resolve unintended pregnancy. The treatment rate of postabortion complications has declined, owing largely to widespread access to misoprostol. This transformation of the abortion landscape calls for concerted efforts to increase contraceptive use and strengthen postabortion care.